Root Cause Analysis (RCA) of Global Wheat Price Volatility: A Study of Influential Factors Amidst the 2022 Russia-Ukraine Conflict - Kumara, Aditya; Octavian, Amarulla; Swastanto, Yoedhi; Laksmono, Rudi (UNIVED Press, 2026)
The 2022 Russia-Ukraine conflict triggered significant disruptions to global food stability. As wheat producers accounting for 34.1% of the world's supply, the conflict caused prices to surge to 1400 per ton in March 2022, up from a previous average of 800–900 per ton. The most severe impact was felt in the heavily import-dependent Middle East and North Africa (MENA) region, affecting countries such as Somalia (100%), Egypt (84%), and Sudan (75%).This research utilizes Root Cause Analysis (RCA) based on a literature review to identify the root causes of the crisis. The findings point to three primary factors: export restrictions (the Black Sea blockade), damage to agricultural infrastructure, and a reduction in human resources. Recommended solutions include diversifying food sources, establishing strategic reserves, and strengthening domestic food security. These findings underscore the need for a structural approach, rather than merely short-term mitigation, in confronting global food crises.